The Constituent Dynamic and the Two-Level Game in Chile. - Fuentes, Claudio; Valenzuela, Pedro; Carril, Francisca (Latin American Research Review, 2026)
Chile has undergone two consecutive failed attempts at constitutional replacement (2021–2022 and 2023), positioning it as a globally interesting case. While existing literature identifies macropolitical and institutional factors underlying such failures, certain key causal mechanisms remain unexplored. This article addresses the central question of why majority-controlling political actors, aware of the need for broad national consensus, ultimately fail to achieve it. Framed as a two-level process—one at the elite negotiation level and the other at the electoral ratification level—this study elucidates the mechanisms operating at each stage that contributed to this dual failure. By analyzing these dynamics in detail, the article offers valuable lessons for future efforts to replace a constitution in a democratic setting.